The organized teacher's guide to classroom management - Springer, Steve; Persiani-Becker, Kimberly (McGraw Hill, 2011)
"As a teacher, you have the ability to positively shape your students? future. This book will give you tools and advice to help you fulfill your passion for teaching and help your students succeed."